DINAMIKA PROSES PEMEKARAN KECAMATAN SENTAJO RAYA KABUPATEN KUANTAN SINGINGI TAHUN 2008-2012 - ZULKARNAIN, ARIANDI A; Tinov, M. Y. Tiyas (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Regional growth is a form of regional autonomy that should be supported by all elements of the local and central levels of society , which is based on Law No. 32 of 2004 and Law 19 of 2008 which has been set up how terotori policy laid out in the merger , abolition , and expansion . Subdistrict Sentajo Kingdom in full formation of political nuances and dynamics of a number of public rejection of the District Benai . Departing from the above phenomenon researchers are interested in studying the formation of the District Sentajo Kingdom with the title